2005
DOI: 10.1063/1.1896449
|View full text |Cite
|
Sign up to set email alerts
|

GaN-based anion selective sensor: Probing the origin of the induced electrochemical potential

Abstract: The gallium nitride (GaN) semiconductor has been used as the sensing element in a chemical sensor for the measurement of charged species in solution. The sensor shows remarkable selectivity for anions, such as sulphate (SO42−) and hydroxide (OH−). It is shown that the GaN surface interacts selectively with Lewis bases as shown by impedance spectra. In addition, both the impedance spectra and the surface induced potential of the sensor element correlate very well with the activity of both the negatively charged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
(18 reference statements)
2
22
0
Order By: Relevance
“…51.9 AE 3.7 mV/decade and are generally consistent with those reported by Chaniotakis [13,14]. The largest difference occurs for KSCN (À 51.9 AE 3.7 mV/decade in our study versus À 69.5 mV/decade in Chaniotakis [13,14] ).…”
Section: Calibration Plotssupporting
confidence: 94%
See 3 more Smart Citations
“…51.9 AE 3.7 mV/decade and are generally consistent with those reported by Chaniotakis [13,14]. The largest difference occurs for KSCN (À 51.9 AE 3.7 mV/decade in our study versus À 69.5 mV/decade in Chaniotakis [13,14] ).…”
Section: Calibration Plotssupporting
confidence: 94%
“…The linear regions of the GaN electrode in this research are generally of similar magnitude or wider than those reported by Chaniotakis [13,14] with the same electrolyte solutions.…”
Section: Calibration Plotssupporting
confidence: 56%
See 2 more Smart Citations
“…Chaniotakis [11] used EIS experiments to show that the potentiometric sensitivity of GaN electrodes is controlled by the Helmholtz and Gouy layers formed at the GaN/ electrolyte interface. To our knowledge, the origin of the interfacial potential observed at In 0.2 Ga 0.8 N electrodes/ solution phase boundary has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%